Brushstrokes as art’s unique signature east and west / Masahiro Suda - Suda, Masahiro (Universiti Teknologi MARA, Perak, 2018)
Painting does not have all that much influence in contemporary art exhibitions today, as most of them are devoted to installations, often featuring digital arts. Yet, painting still matters as a straightforward display of artistic spirit, as much as an original signature matters when it comes to our paper documents. Brush marks play a key role in painting, as shown by many historical examples of their unique, mutual relation.